The Functional Movement Screen: Exploring Interrater Reliability between Raters in the Updated Version - Ricky Morgan; Steven LeMire; Lindsey Knoll; Emily Schuster; Cooper Tietz; Austin Weisz; Gary Schindler (International Journal of Sports Physical Therapy)
# Background